Restriction of Rice Portion and Pre-Meal Fruit with HbA1c Levels and Abdominal Fat for Diabetics in Malang City: Pembatasan Porsi Nasi dan Konsumsi Buah Sebelum Makan dengan Kadar HbA1c dan Lemak Perut Penderita Diabetes Mellitus Tipe-2 di Kota Malang - Dwipajati, Dwipajati; Kaswari, Sutomo Rum Teguh (Amerta Nutrition, 2024)
Background: Glycemic control is the basis for managing diabetes to prevent chronic complications in diabetes.HbaA1c levels reaching â‰¤7% is an indicator of achieving good glycemic control. The 3J principles (right type, amount, and schedule) in the pillars of meal management are not easy to apply, causing diabetes to have difficulty achieving glycemic targets. Objectives: Analyzing rice portion restriction and pre-meal fruit with HbA1c levels and abdominal fat in people with diabetes in Malang City. Methods: Experimental study type 'randomized controlled trial' with pre-posttest control group design involved 16 people with diabetes who were active in Prolanis activities at the Malang city health center. Respondents were randomly divided into 2 groups. HbA1c levels were taken 2 times, before and after the intervention. The t test and paired t test with a pvalue<0.05 were used to test the effect of the intervention on HbA1c levels, abdominal fat and abdominal circumference in people with diabetes for 3 months. Results: Both forms of intervention can reduce HbA1c levels in diabetic patients. Limiting the portion of rice significantly reduced HbA1c levels (p=0.003) and visceral fat levels. However, determining the amount of rice with added pre-meal fruit did not significantly decrease visceral fat and abdominal circumference (p>0.05). Conclusions: Limiting the portion of rice eaten by itself or combining it with pre-meal fruit may help diabetics lower their HbA1c levels.